2016
DOI: 10.1002/aenm.201502147
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring a New 4V‐Class Cathode Material for Na‐Ion Batteries

Abstract: 8C, retaining 84% of its initial capacity in its micrometer-sized particle morphology. Na 7 V 3 (P 2 O 7 ) 4 was successfully synthesized for the fi rst time using the Na-phosphate fl ux method (see the Experimental Section in Supporting Information for details). Note that excess amount of Na-phosphate were used and then washed with water. [ 27 ] The structural characterization based on Rietveld refi nement of X-ray diffraction (XRD) in Figure 1 a reveals that Na 7 V 3 (P 2 O 7 ) 4 has the C2/ c space group wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…A new V-based pyrophosphate cathode material, Na 7 V 3 (P 2 O 7 ) 4 with a space group of C2/c, was demonstrated by Kim et al [44] It was revealed that Na 7 V 3 (P 2 O 7 ) 4 was capable of delivering an average voltage of 4.13 V, which may represent one of the highest values observed for the V 3+/4+ redox couple in SIBs. The abnormally high operating potential of Na 7 V 3 (P 2 O 7 ) 4 is attributed to a sharing of each corner of the VO 6 octahedra with P 2 O 7 groups (Figure 3e,f).…”
Section: High-voltage Polyanion Positive Electrode Materials Based Onmentioning
confidence: 99%
“…A new V-based pyrophosphate cathode material, Na 7 V 3 (P 2 O 7 ) 4 with a space group of C2/c, was demonstrated by Kim et al [44] It was revealed that Na 7 V 3 (P 2 O 7 ) 4 was capable of delivering an average voltage of 4.13 V, which may represent one of the highest values observed for the V 3+/4+ redox couple in SIBs. The abnormally high operating potential of Na 7 V 3 (P 2 O 7 ) 4 is attributed to a sharing of each corner of the VO 6 octahedra with P 2 O 7 groups (Figure 3e,f).…”
Section: High-voltage Polyanion Positive Electrode Materials Based Onmentioning
confidence: 99%
“…[ 205 ] More recently, Kim et al reported a new V-based pyrophosphate compound, Na 4 V 3 (P 2 O 7 ) 4 , as a cathode for NIBs. [ 207 ] The electrode delivered a capacity of approximately 80 mA h g −1 at a current rate of C/10 with an average voltage of 4.13 V vs Na + /Na. The electrode exhibited the highest V 3+ /V 4+ redox potential among all the V-based polyanionic compounds, which is attributed to the unique structural aspect of VO 6 octahedra sharing every corner with a P 2 O 7 group, maximizing the inductive effect in the structure.…”
Section: (14 Of 38)mentioning
confidence: 99%
“…[205][206][207] Barpanda et al fi rst introduced tetragonal Na 2 (VO)P 2 O 7 , which yields a reversible capacity of 80 mA h g −1 involving the V 4+ /V 5+ redox reaction at 3.8 V vs Na + /Na. [ 205 ] More recently, Kim et al reported a new V-based pyrophosphate compound, Na 4 V 3 (P 2 O 7 ) 4 , as a cathode for NIBs.…”
Section: (14 Of 38)mentioning
confidence: 99%
“…By far, various cathode materials including layered transition-metal oxides, Prussian blue analogues (PBAs), and polyanion-type compounds have been proposed. [11][12][13] Recently, the Na superionic conductor (NASICON)-structured polyanion-type materials are of significant interest because of their unique crystal framework that is constructed by units of MO 6 octahedrons (M represents transition metals) and XO 4 tetrahedrons (X = P, S, Si, As), building 3D ion channels for fast Na + migration. [5][6][7] On the other hand, the applications of PBAs are limited by their low volume density, inferior thermal stability, and toxicity of cyanide.…”
mentioning
confidence: 99%